Effect of heat treatment on electrical and surface properties of tungsten oxide thin films grown by HFCVD technique - Tan, Guang-Lei (2021)
The present research focuses on the synthesis, characterization, and electrical properties of tungsten oxide thin films deposited using the Hot filament chemical vapor deposition (HFCVD) system on stainless steel 316L substrate. Various characterization tools such as X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy (AFM), and Raman spectroscopy were used to study the structural, morphological, and surface roughness of the samples. The obtained results from XRD demonstrated development of WO2 and WO3 phases and enhancement in the crystallinity upon an increase in the substrate temperature of tungsten oxide thin films. High substrate temperature also caused a low number of defects and dislocation density as well as low micro-strain values. According to SEM results, tungsten oxide thin films composed of closely packed uniform crystal clusters with an improvement in the grain size upon increasing substrate temperature. The acquired AFM images demonstrate increasing grain/cluster size on the surface of deposited thin films and decreasing surface roughness with rising substrate temperature. The Raman spectroscopy results illustrate five distinct stretching vibrational bands of O-W-O which are ascribed to W6+=O stretching mode of terminal oxygen atoms. The obtained results of electrical resistivity using four-probe method demonstrate that the resistivity of films decreases upon an increase in the grain size when the substrate temperature increases. This observation is consistent with the larger grain boundaries and scatter carriers which result in reduction of mobility. This paper provides a facile preparation of tungsten thin films useful for variety of optoelectronic, photovoltaic, and energy storage devices.